2009
DOI: 10.1253/circj.cj-09-0166
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Endovascular Therapy With Nitinol Stent Implantation for TASC II A/B Femoro-Popliteal Artery Lesions 4 Years' Experience

Abstract: lthough the initial success rate of endovascular therapy (EVT) for femoro-popliteal artery (FPA) had been reported as 95% for stenotic and more than 85% for occlusive lesions, 1 mid-and long-term patency has remained an unsolved clinical issue. [1][2][3] Balloon angioplasty, which is the conventional and traditional treatment for FPA lesions, is extremely limited because of its low primary patency rate of 40-60% after 6-12 months. 4,5 Early experience with stainless-steel stents showed no beneficial superiorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…6 Female gender, younger age, diabetes mellitus, no cilostazol, CLI, CTO, TASC II C/D lesion, and stent fracture have been associated with restenosis following nitinol stenting in the SFA. [16][17][18] In this study, female gender and TASC II C/D lesion were more prevalent in the TLR group compared to the no-TLR group on univariate analysis, but age, diabetes mellitus, use of cilostazol, CLI, and CTO were similar between the 2 groups. Previous studies reported that use of cilostazol pre-(25%) were detected on angiogram.…”
Section: Ivus Findingsmentioning
confidence: 50%
“…6 Female gender, younger age, diabetes mellitus, no cilostazol, CLI, CTO, TASC II C/D lesion, and stent fracture have been associated with restenosis following nitinol stenting in the SFA. [16][17][18] In this study, female gender and TASC II C/D lesion were more prevalent in the TLR group compared to the no-TLR group on univariate analysis, but age, diabetes mellitus, use of cilostazol, CLI, and CTO were similar between the 2 groups. Previous studies reported that use of cilostazol pre-(25%) were detected on angiogram.…”
Section: Ivus Findingsmentioning
confidence: 50%
“…Use of nitinol stent for simple lesions may lead to elimination of the need for re-stenosis after the procedure. 16 We found CLI in 11 patients (4.5%) and major amputation was performed in 4 of these (1.6%). Spontaneous CLI has been found in 1-2% of claudicant patients up to 5 years, 2 and occurred in 4.5% (11 patients) within 10 years in the present study.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have emphasized the importance of the quality of the distal run-off tract from the point of view of both technical success and long-term patency. 11,13, 16 According to some studies, occlusion length, distal run-off vessels and smoking are independent risk factors for reocclusion. 1 In a recent study, Setacci et al found that the factors capable of independently affecting patency following SIA for TASC C and D lesions of SFA were renal insufficiency (P=0.03), current smoking (P=0.01), and diabetes (P=0.04).…”
Section: Sia In Tasc C/d Femoropopliteal Diseasementioning
confidence: 99%